2017
DOI: 10.3174/ajnr.a5471
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hemodynamics in Intracranial Bifurcation Arteries after Aneurysm Treatment with Flow-Diverter Stents

Abstract: Anatomic data analysis showed statistically significant correspondence between caliber changes and bifurcation asymmetry characterized by diameter ratio <0.7 ( < .001). Similarly, computational fluid dynamics results showed the highest impact on hemodynamics when flow-diverter stents are deployed in asymmetric bifurcations (diameter ratio <0.65) with noticeable changes on wall sheer stress fields. Further research and clinical validation are necessary to identify all elements involved in vessel caliber changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
(36 reference statements)
0
12
0
Order By: Relevance
“…The aim of the study was to investigate, for a cohort of 142 aneurysm datasets, the role of resistance to flow in flow changes induced by FDS treatment that may relate to vessel narrowing/occlusion in a subacute phase. The effect of FDS on flow distribution at symmetric and asymmetric bifurcations has been studied previously, but this was compared with a small number of cases (25), which was not enough to explain the changes in vessel diameter 13…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The aim of the study was to investigate, for a cohort of 142 aneurysm datasets, the role of resistance to flow in flow changes induced by FDS treatment that may relate to vessel narrowing/occlusion in a subacute phase. The effect of FDS on flow distribution at symmetric and asymmetric bifurcations has been studied previously, but this was compared with a small number of cases (25), which was not enough to explain the changes in vessel diameter 13…”
Section: Discussionmentioning
confidence: 99%
“…Blood was assumed incompressible (density ρ =1050 kg/m 3 ) and Newtonian (viscosity μ =0.0035 Pa.s). Appropriateness of modeling approaches and accuracy of the numerical solutions were ensured by adopting methodologies that we have previously reported 13 18 20 21. The mesh used for the unstented model comprised approximately 0.8 million nodes (4 million nodes for the stented model) and 2.7 million elements (19 million elements for the stented model), resulting in a mesh volumetric density of 2.7 thousand elements per mm 3 (19 thousand elements per mm 3 for the stented model).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[6,13] Other researchers present data supporting the fact that asymmetrical distal vessels (daughter vessels) influence the flow dynamics in the area of a bifurcation. [4,17] As a result, it could be assumed that this is associated with a higher incidence of aneurysm development at the affected bifurcations. To further support this, Zhang et al demonstrated in 2019 that asymmetric MCA bifurcations are more susceptible to the development of aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…As 0-D models are less costly than 1-D models, a Windkessel model is often used to provide boundary conditions for 1-D blood flow simulation [46,47,52]. A coupling of a 1-D and 3-element Windkessel model proposed by Reymond et al [47] was adopted in several studies on aneurysm CFD for the purpose of specifying boundary conditions [53][54][55]. Another way to utilise a 0-D model is to acquire outflow boundary conditions for 3-D haemodynamic simulation directly, not via any 1-D model.…”
Section: Reduced-order Modelsmentioning
confidence: 99%